Isolation and identification of Bacteria and their drug susceptibility pattern in children to establish the correlation between childhood Septicemia with C-reactive protein (CRP) levels (Journal of Bio-Science, 2015)
Context: Neonatal sepsis is one of the most important causes of morbidity and mortality and C-reactive protein (CRP) an excellent biomarker has significant diagnostic and prognostic value for the treatment of septicemia patient. Objectives: To isolate and identify viable pathogens from blood culture and their antibiogram and to correlate CRP levels with septicemic child. Materials and Methods: A total of 273 cases among which 233 were clinically suspected septicemia cases and 40 were healthy controls in age group 0 day to 15 years were selected from United Hospital Ltd., Dhaka Bangladesh. Blood culture was analyzed by the instrument BACTEC 9120 series. CRP was measured from blood serum by the auto biochemical analyzer OLYMPUS AU 640 followed by immuno-turbidimetric method. The organisms were isolated by inoculation on blood agar and MacConkey agar media. Identification of the organisms was done by colony morphology, gram staining and biochemical tests. Sensitivity of isolates was done against antimicrobial agents by disc diffusing method. Results: Blood samples in total 233 cases of suspected septicemia in children were studied between the ages of 0 day to 15 years. Culture proven septicemia 39 (16.74%), probable septicemia 136 (58.37%) and nonsepticemic febrile patients 58 (24.90%) were found. The highest rate of blood culture positivity found among 5-10 yrs. age group (25.64%). Salmonella typhi (41.03%) was the most common infective agent. The rate of blood culture positivity was significantly higher (p6 mg/l) and p value significant (p